2017
DOI: 10.1088/1748-605x/aa52ca
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent cytotoxicity evaluation of graphite nanoparticles for diamond-like carbon film application on artificial joints

Abstract: While a diamond-like carbon (DLC)-coated joint prosthesis represents the implant of choice for total hip replacement in patients, it also leads to concern due to the cytotoxicity of wear debris in the form of graphite nanoparticles (GNs), ultimately limiting its clinical use. In this study, the cytotoxicity of various GN doses was evaluated. Mouse macrophages and osteoblasts were incubated with GNs (<30 nm diameter), followed by evaluation of cytotoxicity by means of assessing inflammatory cytokines, results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…32 Liao et al found that the cell viabilities decreased in a dose-dependent manner (10-100 μg/ml) and steeply declined at concentrations greater than 30 μg/ml for graphite nanoparticles. 33 In the current study, the results of the MTT and LDH assays conducted on RAW264.7 cells suggested that Mg(OH) 2 NPs at their MICs (4.4 μg/ml) had no significant effect on the biological activity of macrophages. E. coli cells were found to be more vulnerable to Mg(OH) 2 NPs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…32 Liao et al found that the cell viabilities decreased in a dose-dependent manner (10-100 μg/ml) and steeply declined at concentrations greater than 30 μg/ml for graphite nanoparticles. 33 In the current study, the results of the MTT and LDH assays conducted on RAW264.7 cells suggested that Mg(OH) 2 NPs at their MICs (4.4 μg/ml) had no significant effect on the biological activity of macrophages. E. coli cells were found to be more vulnerable to Mg(OH) 2 NPs.…”
Section: Discussionmentioning
confidence: 53%
“…Hussain et al showed that Fe 3 O 4 , Al, MoO 3 , and TiO 2 nanoparticles had no measurable effects at lower doses (10–50 μg/ml), while significant effects were observed at higher levels (100–250 μg/ml) 32 . Liao et al found that the cell viabilities decreased in a dose‐dependent manner (10–100 μg/ml) and steeply declined at concentrations greater than 30 μg/ml for graphite nanoparticles 33 . In the current study, the results of the MTT and LDH assays conducted on RAW264.7 cells suggested that Mg(OH) 2 NPs at their MICs (4.4 μg/ml) had no significant effect on the biological activity of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Nanocrystalline diamond (NCD) has shown good results after millions of cycles in wear simulators [3,15,16,17]. DLC is a coating with high hardness and a low coefficient of friction due to self-lubricating characteristics that has been found to give a reduced metal ion release, but there is a concern of cytotoxicity due to release of graphite nanoparticles [3,18,19,20,21,22]. While ZrN is already in use in knee implants, with an estimated service life between 20–25 years [23,24], there is a lack of coatings showing consistently good results in hip joint replacements, which have a more challenging wear pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability of both mouse osteoblasts and macrophages were affected in a dosedependent manner from these debris, but when graphite nanoparticles exceeded 30 mg/mL, cell cytotoxicity was dramatically increased. 39 The few clinical applications of DLC have been marked by failure, with inferior survivorship in comparison to aluminum oxide heads at 8.5 years and coating delamination likely due to in vivo dissolution of a silicon-containing substrate-adhesion layer. 40 Further study of multilayer DLC with focus on substantiating substrate adhesion is necessary before more clinical trials are justified.…”
Section: 36mentioning
confidence: 99%